Utilização das tecnologias da informação e comunicação, no contexto da web 2.0, na prática docente na educação superior - Calheiros, Dawson da Silva (2009)
The use of Information and Communication Technologies constitutes pedagogical possibilities even more applied in the educational field. It shows a great expansion in the use of digital media and Web 2.0 services through collaborative tools that enable communication and collective formation of knowledge, recreating the traditional roles of professors and students. Based on this scenario, this research investigates the use of the Web 2.0 resources in the pedagogical practice of bachelor s degree professors from the possibilities offered by these tools of technology in the educational environment and through important factors in this process, such as the interaction and collaboration, it is also investigated whether the use of Web 2.0 helps develop cognitive skills in professors and students who use it. The locus of the research involved four schools in the Centro de Estudos Superiores de Maceió: School of Biological Sciences and Health, School of Applied Sciences and Technology, School of Education and Communication and School of Applied Social Sciences. The ones involved were the professors who teach in undergraduate courses at that institution, as well as students of these professors. The methodology used was the case study with a qualitative approach. Being the object of the study are the possibilities of collaboration tools for students and professors, which Web 2.0 features are being used on teaching practice, causes of non-use of tools, the results achieved by those who have included them in their subjects and content of Web 2.0 services and the development of cognitive skills for cyber-education. The results indicate that most professors still do not use the web 2.0 in their practice for reasons such as lack of time or they were not trained. They also indicate that using Web 2.0 in the educational context, professors and students develop cognitive skills that are essential to a good education, where collaboration and interaction are present. The research suggests that institutions of higher education must adopt policies for access and technical and teaching training for educators involved in the context of the new educational reality so more dynamic, interactive classes and real learning will be generated